Exploring aspects of mentoring for black and minoritised healthcare professionals in the UK: a nominal group technique study - Vimal Sriram; Anita Atwal; Elizabeth A McKay (BMJ Open)
Objective Mentoring plays a crucial role in career development, particularly for black and minoritised ethnic (BME) professionals. However, existing literature lacks clarity on the impact of mentoring and how best to deliver for career success. This study aimed to ascertain perceptions and build consensus on what is important in mentoring for BME healthcare professionals.Design Nominal group technique: The participants in the group followed a structured stepwise process of introduction, silent idea generation, each participant presenting ideas in turn, open discussion and priority voting based on common themes generated during the discussion. This was followed by the creation of a model covering the important aspects of mentoring for BME healthcare professionals.Setting UK.Participants A nominal group technique workshop with 12 participants briefed on this technique.Results There was strong agreement about the most highly rated attributes. Participants emphasised the significance of psychosocial mentoring, highlighting trust, intimacy and clear communication of expectations between mentor and mentee. Discussions on race and racism in mentoring were considered essential. Mentoring circles were proposed as complementary to one-to-one mentoring, offering peer support. Participants stressed the importance of allies in the mentoring process, highlighting the need for authenticity, humility and courage in challenging established norms.Conclusion This study helped create a mentoring model tailored to the needs of BME health and care professionals. This model highlights the importance of sponsorship, allyship, surface characteristics and peer support in fostering career progression for BME mentees. Key elements include mentor honesty, humility and awareness of bias and race issues, alongside skills for effective mentoring relationships. This model provides a mechanism for supporting and mentoring BME workers in healthcare for career advancement.